2020
DOI: 10.3390/genes11020138
|View full text |Cite
|
Sign up to set email alerts
|

Control of DNA Damage Bypass by Ubiquitylation of PCNA

Abstract: DNA damage leads to genome instability by interfering with DNA replication. Cells possess several damage bypass pathways that mitigate the effects of DNA damage during replication. These pathways include translesion synthesis and template switching. These pathways are regulated largely through post-translational modifications of proliferating cell nuclear antigen (PCNA), an essential replication accessory factor. Mono-ubiquitylation of PCNA promotes translesion synthesis, and K63-linked poly-ubiquitylation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 82 publications
1
33
0
Order By: Relevance
“…The DNA damage-tolerance pathway that promotes the exchange between replicative and specialized polymerases at stalled forks is known as translesion DNA synthesis (TLS). The recruitment of specialized DNA polymerases to DNA is favored by the ubiquitination of PCNA, thus providing a docking point for ubiquitin-binding domains in specialized DNA polymerases [ 24 , 99 ]. Despite the average poor fidelity of specialized polymerases, certain TLS events are not mutagenic when using specific DNA lesions as replication templates.…”
Section: Cdk-independent Effect Of P21 Overexpression On Damaged Dmentioning
confidence: 99%
“…The DNA damage-tolerance pathway that promotes the exchange between replicative and specialized polymerases at stalled forks is known as translesion DNA synthesis (TLS). The recruitment of specialized DNA polymerases to DNA is favored by the ubiquitination of PCNA, thus providing a docking point for ubiquitin-binding domains in specialized DNA polymerases [ 24 , 99 ]. Despite the average poor fidelity of specialized polymerases, certain TLS events are not mutagenic when using specific DNA lesions as replication templates.…”
Section: Cdk-independent Effect Of P21 Overexpression On Damaged Dmentioning
confidence: 99%
“…4B) (Beckmann et al, 2017). K63 chains are associated with NF-κB signaling which has diverse functions including innate immunity, DNA transcription, autophagocytosis (Tan et al, 2008;Wertz and Dixit, 2010), and proliferation of cell nuclear antigen (PCNA) (Ripley et al, 2020) that has previously been shown to act abnormally in CI-affected embryos (Landmann et al, 2009). A single amino acid mutation in the catalytic site of the Ulp1 prevents the breakdown of ubiquitin chains in vitro (Beckmann et al, 2017).…”
Section: Cifb Molecular Functionmentioning
confidence: 99%
“…Ubiquitin is added to and removed from many proteins directly involved in DNA damage bypass. The proliferating cell nuclear antigen (PCNA) sliding clamp is one such substrate that has essential roles in normal replication as well as in TLS and TS [ 36 ]. Eukaryotic PCNA functions as a heterotrimeric protein, forming a ring-like structure through which dsDNA at the replication fork is encircled [ 37 ].…”
Section: Ubiquitin and Ubiquitin-like Modifiers In Dna Damage Bypamentioning
confidence: 99%